2020
DOI: 10.1212/nxi.0000000000000883
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of paraneoplastic neurologic syndromes and autoimmune encephalitides in France

Abstract: ObjectiveTo determine the observed and expected incidence rates of paraneoplastic neurologic syndromes (PNSs) and autoimmune encephalitides (AEs) diagnosed in France between 2016 and 2018, we conducted a population-based epidemiologic study.MethodsObserved incidence rates were stratified by sex, age groups, region of care, year of diagnosis, and disease subgroups. National expected incidence rates were calculated based on rates obtained in the area directly adjacent to the Reference Center using a mixed Poisso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
68
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 98 publications
(74 citation statements)
references
References 25 publications
5
68
1
Order By: Relevance
“…In our cohort, the sex ratio was close to equal, with NMDAR encephalitis occurring slightly more frequently in men than women. Similar sex ratio was observed in a cohort of Chinese AE patients (12), although, published data claims that anti-NMDAR encephalitis affects predominantly young women (median age, 21 years) (3,22). Dalmau et al (3) reported male predominance in LGI1, GABABR and Caspr2 encephalitis, which was also observed in our cohort, although, the median age of our AE patients were 45-50 years compared to median values of 60-65 years in previous publications (3,23).…”
Section: Discussionsupporting
confidence: 76%
“…In our cohort, the sex ratio was close to equal, with NMDAR encephalitis occurring slightly more frequently in men than women. Similar sex ratio was observed in a cohort of Chinese AE patients (12), although, published data claims that anti-NMDAR encephalitis affects predominantly young women (median age, 21 years) (3,22). Dalmau et al (3) reported male predominance in LGI1, GABABR and Caspr2 encephalitis, which was also observed in our cohort, although, the median age of our AE patients were 45-50 years compared to median values of 60-65 years in previous publications (3,23).…”
Section: Discussionsupporting
confidence: 76%
“…A more useful parameter in clinical practice is the positive predictive value (PPV), which is the ratio between true positives and total positive results obtained by testing a given population, and is highly dependent on the frequency of the disease of interest in the population tested and the test ordering practices (106). This is particularly relevant for rare disorders like autoimmune neurologic disorders, for which the reported overall incidence and prevalence range between 3.5 and 9/million person-years and 4-6.5/100.000 persons, respectively (107)(108)(109). When similar rare disorders are faced, caution is advised in clinical practice as the risk of false positive results is not negligible if the test is performed indiscriminately, despite very high specificity and sensitivity (110).…”
Section: Positive Predictive Value False Positives and "Phenotype Creep"mentioning
confidence: 99%
“…Yet, stated incidence varies from 1.6 to 8.9 per million person-years, suggesting that underdiagnosis and underreporting are still relevant issues. 3,4 It is likely that the expanding use of immune checkpoint inhibitors (ICIs) in oncologic practice will lead to an increased frequency of similar syndromes. 5,6 In 2004, a set of recommended diagnostic criteria for PNS were defined by a panel of international experts and became the standard for clinical and research purposes.…”
mentioning
confidence: 99%